2020
DOI: 10.1097/md.0000000000021115
|View full text |Cite
|
Sign up to set email alerts
|

Primary anaplastic large cell lymphoma of the central nervous system in a child

Abstract: Introduction: To report the clinical characteristics of primary central nervous system T-cell lymphoma with anaplastic lymphoma kinase-1 (ALK-1) positive in an 8-year-old male. Patient concerns: The patient presented cognitive impairment, dizziness, vomiting, fever, and convulsions during the disease, followed by progressive and persistent severe headache, progressive increase of intracranial pressure, indifference, disorder of consciousness, mild increase in white bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Involvement of the brain parenchyma in cases of ALK + ALCL is a rare event, with few reports of primary involvement 3 4 5 6 7 and even fewer of secondary involvement. 8 9 10 One study 11 analyzed the ALCL99 database, which comprises data on 618 patients with confirmed CNS biopsy between 1999 and 2017, involving 175 centers across 11 European countries and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the brain parenchyma in cases of ALK + ALCL is a rare event, with few reports of primary involvement 3 4 5 6 7 and even fewer of secondary involvement. 8 9 10 One study 11 analyzed the ALCL99 database, which comprises data on 618 patients with confirmed CNS biopsy between 1999 and 2017, involving 175 centers across 11 European countries and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…CNS involvement in children with ALCL is also extremely rare, both as primary and secondary localization: in an international study of systemic childhood ALCL [21], CNS disease was recognized in only 2.6% of cases, most of them being secondary involvement. After a review of English literature, we identified 23 pediatric cases of primary CNS ALCL (Table 4) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Age ranged from 23 months to 18 years (median 11 years).…”
Section: Discussionmentioning
confidence: 99%
“…Only other nine pediatric cases of primary CNS ALCL were reported in literature (Supporting Materials, Supplemental Table S1). [4][5][6][7][8][9][10][11][12] In five out of nine, the initial clinical suspicion concerned an infectious disease (Supporting Material S2).…”
Section: Primary Central Nervous System Anaplastic Large Cell Lymphom...mentioning
confidence: 99%